Risk Factors of Ischemia Reperfusion Injury After PCI in Patients with Acute ST-Segment Elevation Myocardial Infarction and its Influence on Prognosis - Zhang, Li; Wang, Lingqing; Tao, Luyuan; Chen, Changgong; Ren, Shijia; Zhang, Youyou (Frontiers in Surgery, 2022)
Purpose To explore the risk factors of ischemia reperfusion injury (IRI) after percutaneous coronary intervention (PCI) in patients with acute ST-segment elevation myocardial infarction (STEMI) and its influence on prognosis. Methods The clinical data of 80 patients with STMEI undergoing PCI in our hospital from June 2020 to June 2021 were collected. According to whether IRI occurred after PCI, STMEI patients were divided into IRI group and non-IRI group. The basic information, clinical characteristics, examination parameters and other data of all patients were collected, and the prognosis of the two groups was observed. Risk factors were analyzed by fitting binary Logistic regression model. The survival prognosis was analyzed by Kaplan-Meier survival curve. Results Logistic regression analysis showed that type 2 diabetes mellitus (T2DM), pre-hospital delay time (PHD) and door-to-balloon expansion time (DTB) were the influencing factors of IRI in patients with STMEI (p < 0.05). MACE occurred in 11 cases (32.35%) in the IRI group and 13 cases (28.26%) in the non-IRI group. Log-rank test showed p = 0.503, indicating no statistically significant difference. Conclusion T2DM, PHD and DTB were the influencing factors of IRI in patients with STMEI, and IRI will not reduce the prognosis of patients.